Pengaruh Keselamatan dan Kesehatan Kerja Karyawan terhadap Produktivitas Kerja Karyawan Bagian Gudang PT Muara Dua Kota Palembang - Zulfikar, Muhammad; Wadud, Muhammad; Kurniawan, M. (Jurnal Nasional Manajemen Pemasaran dan SDM, 2022)
This study aims to investigate the effects of safety and health of employees on work productivity of employees at the warehouse of PT Muara Dua Palembang. Data of 65 respondents were collected through a questionnaire. This study applied the multiple linear regression to analyze the data. The findings unveil that partially work safety has a significant and negative effect on employees' work productivity. Additionally, employees' occupational health has a significant and positive effect on work productivity. Simultaneously, occupational safety and health have a significant and positive effect on employees' productivity. This empirical evidence can provide benefits for PT Muara Dua Palembang. To increase employees' productivity, the leader of the company should optimize the safety and health factors of employees.